Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Solid chromium (III) hydroxide reacts with nitric acid. Write the balanced net ionic equation.?
Cr(OH)3(s) + 3HNO3(aq) --> Cr(NO3)3(aq) + 3H2O(l)
This is the correct balanced chemical equation.
I have tried entering both:
3OH-(aq) + 3H+(aq) --> 3H2O(l)
3OH-(s) + 3H+(aq) --> 3H2O(l)
But neither are marked correct. Could someone please tell me what is wrong with my answer?
OH-(s) + H+(aq) --> H2O(l)
OH-(aq) + H+(aq) --> H2O(l)
Are also incorrect
Cr(OH)3(s) + 3H+(aq) --> 3H2O(l) + Cr{3+}(aq)
Is apparently the answer... can someone explain why? The Chromium doesn't have a change in charge.
8 Answers
- 1 decade agoFavorite Answer
You cannot take a solid apart. The solid has to be together.
You have to keep the solid and then take out the spectator ions,which would be nitric acid.
Cr(OH)3 (s)+ 3H+ (aq) --> Cr3+ (aq) +3H2O
- 6 years ago
This Site Might Help You.
RE:
Solid chromium (III) hydroxide reacts with nitric acid. Write the balanced net ionic equation.?
Cr(OH)3(s) + 3HNO3(aq) --> Cr(NO3)3(aq) + 3H2O(l)
This is the correct balanced chemical equation.
I have tried entering both:
3OH-(aq) + 3H+(aq) --> 3H2O(l)
3OH-(s) + 3H+(aq) --> 3H2O(l)
But neither are marked correct. Could someone please tell me what is wrong with my answer?
Source(s): solid chromium iii hydroxide reacts nitric acid write balanced net ionic equation: https://shortly.im/0P62X - Anonymous5 years ago
(b) Solid chromium (III) hydroxide reacts with nitrous acid. Cr(OH)3 (s) + 3HNO3(aq) → Cr(NO3)3(aq) + 3H20(l) Cr(OH)3(s) + 3H(+)(aq) + 3NO3(-)(aq) → Cr(+3)(aq) + 3NO3(-)(aq) + 3H2O(l) Cr(OH)3(s) + 3 H(+)(aq) → Cr(3+)(aq) + 3H2O(l)
- How do you think about the answers? You can sign in to vote the answer.
- Anonymous7 years ago
Cr(OH)3(s)+3HNO2(aq)→Cr3+(aq)+3NO2−(aq)+3H2O(l)
- 5 years ago
The Correct Answer is:
Cr(OH)3 (s) + 3HNO2 (aq) ---> 3H2O (l) + Cr3+ (aq) + 3NO2- (aq)
- 7 years ago
Cr(OH)3(s)+3HNO2(aq)→3H2O(l)+Cr3+(aq)+3NO2−(aq)
I can't explain it, but I know it's right because the computer program we use for homework told me so. Our school uses Mastering Chemistry. So if anyone has this question now a days, please write this as their answer. I am 100% positive it's right.